2022
DOI: 10.3389/fmicb.2022.845625
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of RNA Modifications in the Regulation of Antiviral Innate Immunity

Abstract: Posttranscriptional modifications have been implicated in regulation of nearly all biological aspects of cellular RNAs, from stability, translation, splicing, nuclear export to localization. Chemical modifications also have been revealed for virus derived RNAs several decades before, along with the potential of their regulatory roles in virus infection. Due to the dynamic changes of RNA modifications during virus infection, illustrating the mechanisms of RNA epigenetic regulations remains a challenge. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 165 publications
(198 reference statements)
0
18
0
Order By: Relevance
“…Surveys of modified residues in virus mRNAs have recently found methyl groups attached not only to the few 5′-terminal residues, but also to the nucleosides (the base or the sugar) in the mRNA body (recently reviewed in [ 75 , 76 ]). Neither the extent and site-specificity of those modifications, nor their biological functions have been sufficiently studied.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of modified residues in virus mRNAs have recently found methyl groups attached not only to the few 5′-terminal residues, but also to the nucleosides (the base or the sugar) in the mRNA body (recently reviewed in [ 75 , 76 ]). Neither the extent and site-specificity of those modifications, nor their biological functions have been sufficiently studied.…”
Section: Discussionmentioning
confidence: 99%
“…The growing awareness of the potential that epitranscriptomics has for transcript regulation requires further investigation into its role in the innate immune response, and sensing in particular. Previous work has revealed that RNA cap methylations are important in self/non-self RNA discrimination [80][81][82][83]. Indeed, while capped cellular mRNAs do not trigger immune responses, uncapped pathogenic RNAs are recognized by cellular sensors and activate the IFN-I response [69,84].…”
Section: Viral Epitranscriptomics and Innate Immunitymentioning
confidence: 99%
“…Hence, since 2015, multiple studies have explored and investigated the role of epitranscriptomic modifications during viral infection. These studies pointed out that (i) genomic viral RNA can be modified, and that these modifications have a significant impact on their viral life cycle; (ii) viral transcripts can be methylated by the cellular machinery, and (iii) the general epitranscriptomic landscape of the cell changes rapidly during infection, either to promote viral replication by virus-mediated hijacking, or to respond to the invading pathogen and prevent its replication through innate defense mechanisms [59,83,99]. These observations paved the way for further investigations into the possible roles of epitranscriptomic modifications in tuning the antiviral response, which is the focus of the present work (Table 1).…”
Section: Viral Epitranscriptomics and Innate Immunitymentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A), one of the most abundant epitranscriptomic modifications of messenger RNA (mRNA) and non-coding RNA (ncRNA) in eukaryotic cells, is its main substrate, making FTO the first m 6 A demethylase identified [6] . m 6 A modifications regulate almost every stage of RNA metabolism [7] , which in turn affects many biological processes including metabolism [8] , innate immunity [9] , DNA repair [10] , and programmed cell death [11] , as well as various diseases including obesity [12] and many types of cancers [13] . Not surprisingly, FTO, as one of only two known m 6 A erasers [14] , plays an important role in all of these biological processes and human diseases, particularly in cancers [15] .…”
Section: Introductionmentioning
confidence: 99%